Designs of Soviet war monuments, 1941–1945: transformation of the memorial genre, the models, the visual language and its sources. - Bass Associate Professor, Vadim (Zeitschrift für Slawistik, 2021)
The article examines Soviet memorial designs of the Great Patriotic War period (1941–1945). These monuments were unorthodox in terms of visual language, and they differed strikingly from the Stalinist neoclassical mainstream of the previous decade. Architects tried to find means of commemoration of the enormous tragedy of war that they faced. Analysis of the poetics of their designs along with the commonplaces of the respective critical discourse reveals the process whereby the memorial genre was transformed. This article discusses the monumental tradition developed by the 1940 s, the models, the sources of motifs and solutions, and some stylistic and architectural peculiarities characteristic of wartime projects. Whereas previously the Soviet architects from the early 1930s had been working on the 'ultimate' monument – the Palace of Soviets in Moscow – with the beginning of the war they shifted to improvising in order to 'stretch' the limits of genre. I examine the ways in which they broke the limits and shaped the dense, overwhelming memorial narrative to be transmitted by the monuments. New memorials were considered as a form of heroic epic, analogous to the literary epics but expressed by means of architecture and sculpture. The nationalistic sentiments typical of the war years were reflected in both the design ideology and the perception of memorials. Alongside persistent motifs (such as 'prancing' tanks) emerged new themes (the commemoration of victims along with heroes). The technique of provoking the viewer's emotions, as well as the visual language and architectural style of some structures and particular solutions (such as massive stone cubes), demonstrate the inheritance from the post-Revolutionary Modernist architecture. This unorthodox stylistic flexibility illustrates the 'liberation' of architects – and the short cultural 'liberalization' on the wartime period.